1996
DOI: 10.1177/036354659602400203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fatigue in Susceptibility to Acute Muscle Strain Injury

Abstract: We investigated the role of fatigue in muscle strain injuries using the extensor digitorum longus muscles of 48 rabbits. The muscles of the rabbits were fatigued by 25% or 50% then stretched to failure and compared with the contralateral controls. Three rates of stretch were used. The force to muscle failure was reduced in the fatigued leg in all groups (range, 93% to 97.4% compared with the controls). The change in muscle length in the fatigue groups was not different from the controls. The amount of energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
188
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(198 citation statements)
references
References 24 publications
6
188
1
3
Order By: Relevance
“…4 Also, competition often features stronger muscle contractions coupled with greater fatigue relative to practice settings, thereby placing athletes at greater risk for muscle strains. 10,21 However, nearly 4 times as many quadriceps strains were reported in practices than in competitions, which is most likely the result of far larger numbers of practices than competitions across a season. In both practice and competition settings, athletes should take the time to perform an active warm-up before activity and conclude with postactivity stretching to decrease the risk of injury associated with stiffness and length asymmetries.…”
Section: Event Typementioning
confidence: 99%
See 1 more Smart Citation
“…4 Also, competition often features stronger muscle contractions coupled with greater fatigue relative to practice settings, thereby placing athletes at greater risk for muscle strains. 10,21 However, nearly 4 times as many quadriceps strains were reported in practices than in competitions, which is most likely the result of far larger numbers of practices than competitions across a season. In both practice and competition settings, athletes should take the time to perform an active warm-up before activity and conclude with postactivity stretching to decrease the risk of injury associated with stiffness and length asymmetries.…”
Section: Event Typementioning
confidence: 99%
“…It is also common for athletes to experience the greatest total training volume during the preseason, which may cause fatigue that places athletes at greater risk for strains. 10,21 Injury Mechanism…”
Section: Time In Seasonmentioning
confidence: 99%
“…Sustained loading may increase strain on the injured soft tissues, promoting muscle fatigue 7) . A fatigued muscletendon unit is more susceptible to stretch injury, resulting in a predisposition to LE 11) .…”
Section: Introductionmentioning
confidence: 99%
“…22,49 Two reviews suggested that stretching before strenuous exercises may increase the risk of injury. 44,51 Based on the suggestion by Mair and colleagues 30 that a muscle's ability to absorb eccentric energy is critical to avoid injury, Shrier 44 hypothesized that, if stretching reduced eccentric muscle strength, the muscle may be predisposed to strain-related injuries because it would not be able to prevent excessive sarcomere lengthening. To our knowledge, only 1 previous study 12 tested this hypothesis, and the authors concluded that static stretching did not affect eccentric torque production in women.…”
mentioning
confidence: 99%